EKSISTENSIALISME JEAN PAUL SARTRE (HUKUM ISLAM SEBAGAI ALAT KONTROL KEBEBASAN EKSISTENSI MANUSIA) - Taqbir, A. Afri; Jamil, Jamal; Ilyas, Musfika (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
Human speaking, cannot be separated from the problems inherent in him, namely his awareness and freedom in existence or existence. Jean Paul Sartre is one of the radical figures in existentialism who believes that humans are freedom itself and cannot be limited by even God. The premise of existentialism is that existence precedes essence, which means that humans are nothing until they establish themselves as they wish. This means that humans are not creatures whose nature or essence has been determined, such as things. We can see the landscape of Sartre's thought when human freedom in existence then overlaps with each other to negate the freedom of one of them. On the basis of such problems, Islamic law is here to provide answers to the problems of the ummah where humans can exist and actualize their freedom without denying freedom outside themselves. This type of research is library research, namely research conducted by browsing several literatures on Existentialism, especially Jean Paul Sartre's literature on Existentialism and Humanism.Keywords: Existentialism, Islamic Law, Jean Paul Sartre,Humans.